TRANSFORMATIVE LEADERSHIP IN POLITICAL PARTIES LIFE, IN THE ERA OF DIGITAL DEMOCRACY - Dave Akbarshah Fikarno (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This research is based on the finding of KPK data, during 2004 - 2020 there were 257 corruption cases involving political elites and party leaders as well as regional heads, as well as 297 corruption cases involving private parties. The involvement of the private sector as perpetrators of corruption is due to their interests related to licensing. From this data, a common thread can be drawn, it turns out that many leaders are transactional among political parties and this needs to be reformed to become transformational leaders. The purpose of this research is to want to see problems and problems theoretically, then describe the problems that arise in a description so that later a qualitative conclusion is drawn. The research that he conducted found that there is a strong impression that political parties in the country are still led by transactional leaders rather than transformational ones. Political parties have not succeeded in carrying out their political functions and roles optimally, both related to political education, political communication, political recruitment, political aggregation and articulation, to party involvement in resolving conflicts in society. digital democracy, social media, conversational media, to face-to-face deliberation, have been replaced by smart phone devices that remove barriers, as well as distance between citizens, this makes moving faster and more efficient, low-cost, and able to reach a wide area. The rise of primordial and primordial issues based on ethnicity, religion, race, and inter-group (SARA), in the context of digital democracy must be anticipated and treated as a natural thing.